A comparative study on the adsorption and desorption characteristics of flavonoids from honey by six resins. (1st December 2018) - Lv, Cheng; Yang, Jie; Liu, Rui; Lu, Qun; Ding, Yue; Zhang, Jiuliang; Deng, Jianling
Highlights: AB-8 had good adsorption/desorption capacities of flavonoids from honey. Freundlich and pseudo-second-order model was suitable to the adsorption process. The best temperature of AB-8 resin on the purification of flavonoids was 25 °C. The adsorption process was spontaneous and exothermic. This study provides a practical option for purification of flavonoids from honey. Abstract: The adsorption and desorption characteristics of six different resins (NKA-9, XAD-2, AB-8, D3520, DM-130 and Polyamide) were investigated, in order to screen one resin compared favorably with XAD-2 resin for the purification of flavonoids from honey. The adsorption capacity was XAD-2 > AB-8 > DM-130 > D3520 > NKA-9 > Polyamide, and the desorption ratios of XAD-2, AB-8 and DM-130 had no significant differences, which was higher than those of D3520, NKA-9 and Polyamide. By analyzing kinetic adsorption using pseudo-first-order, pseudo-second-order and particle diffusion kinetics models combined with kinetic desorption, the adsorption and desorption behavior of AB-8 was similar to that of XAD-2, which was excellent than other four resins. The optimal temperature for XAD-2 and AB-8 to adsorb flavonoids was 25 °C under the analysis of Langmuir and Freundlich isotherms models. AB-8 resin offers an efficient and economical choice for the purification of flavonoids from honey.